2018
DOI: 10.1002/qua.25835
|View full text |Cite
|
Sign up to set email alerts
|

Prelude to molecular dynamics: Topography‐driven gaussian charge models

Abstract: A new strategy to develop Gaussian charge models (GCMs) for molecules like ammonia, water, ethene, hydrogen sulfide, formaldehyde and benzene is presented. These molecular models comprising of positive point charges and negative Gaussian charge distributions (GCDs), which represent nuclei and continuous electron charge distribution, are found to correctly represent the ab initio Molecular Electrostatic Potential (MESP) and reproduce its essential topographical features of corresponding molecules. The models us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…For the molecular electrostatic potential (MEP) surface analysis, the molecular structures of arbutin and the solvents were first optimized by the DFT method in Gaussian software, 30 and the wave functions were obtained by the 6-311G++ (d, p) with the basis set of B3LYP. 31 Based on the wave functions, Multiwfn 3.7 was carried out for the MEPs analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For the molecular electrostatic potential (MEP) surface analysis, the molecular structures of arbutin and the solvents were first optimized by the DFT method in Gaussian software, 30 and the wave functions were obtained by the 6-311G++ (d, p) with the basis set of B3LYP. 31 Based on the wave functions, Multiwfn 3.7 was carried out for the MEPs analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular Electrostatic Potential (MEP) Surface Analysis. The molecular structures of MPV and solvent molecules were optimized using Gaussian 09 software, 34 and the wave functions were obtained by B3LYP with the basis set of 6-311G++ (d,p). The molecular electrostatic potential (MEP) isosurface's local minimum and maximum potential sites were generated using Multiwfn 3.8 software 35 and the VMD 1.9.3 program.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…In both: C 6 H 6 …H 2 O and benzene-ammonia (C 6 H 6 …NH 3 ) complexes, one of the hydrogen atoms belonging to H 2 O and NH 3 molecules is found to interact with the π cloud of aromatic substrate ( The underestimated IE s , [18] reported for several stationary points along PES of C 6 H 6 …H 2 O complex at MP2/6-31G(d,p) level of theory (Table 4, column 2) have been rectified (Table 4, column 4) by using vdW/spherical enclosures for respective GCMs. These stationary points were also optimized at MP2/ 6-31 + G(d,p) level of theory and corresponding geometries are displayed in column 5 of Table 4.…”
Section: Interaction Of Benzene With Water Ammonia and Acetylene Molmentioning
confidence: 99%
“…[17] The earlier study from our laboratory dealt with development of topography-based GCMs and demonstrated their reliability to be employed for molecular dynamics simulations as they were capable of predicting correct geometries of water dimer (H 2 O) 2 and benzene-water complex (C 6 H 6 …H 2 O). [18] In continuation with the same, the present study aims in rectifying the underestimated IE values reported for mentioned molecular systems and investigating potential energy surfaces (PESs) of several other interacting molecules using GCMs.…”
Section: Introductionmentioning
confidence: 97%